Factors Related To Dental Caries Among The Patients Attending At The Outpatient Department (OPD) Of Dhaka Dental College And Hospital - Khan, MHA; Polan, MAA; Nahar, A; Raihan, MM (Bangladesh Journal of Dental Research & Education, 2013)
<!--[if gte mso 9]> <![endif]--> Dental caries is one of the most common health problem in the dental practices in both developed and developing countries including Bangladesh. The overall influence of dental caries on the general health of the community is harmful. The main objective of the study was to assess the factors related to dental caries among the patients attending at the Outpatient Department (OPD) of Dhaka Dental College and Hospital. The study was carried out during the month of January to June, 2002. Data were collected by the researcher himself with a pretested structured interview schedule from 167 patients selected by systematic random sampling procedure. The study showed that (29.3%) patients were in the age group of 21-30 years. Their mean age was 30.04 years, SD was ±14.60 and age range was 12-72 years. Among the patients, 55.1% were males and 44.9% were females. 76.6% patients were Muslims, 15.6% were Hindus, and only 7.8% were Christians. Regarding the educational level, the maximum (63%) were below HSC education level, only 37% were HSC and above. The patients having more than four affected teeth, maximum (34.3%) were from illiterate mothers. Patients having mother's education HSC and above were nil in this group. The rates of dental caries were high among those who consumed excess sweets and who did not maintain oral hygiene adequately. Majority of the patients knew how dental caries occur and maximum of them thought that dental caries is a preventable disease. The above study showed that no age and sex is without problem. The ignorance, illiteracy, low family income, inadequate practice of oral hygiene, consumption of excess sweets etc. are the major contributory factors for the occurrence of dental caries. As dental caries is a multifactorial preventable disease, proper preventative measures including health education programme should be intensified to minimize the disease. Further study is also needed to assess the status of the problem and to find out the factors related to the disease. DOI: http://dx.doi.org/10.3329/bjdre.v3i1.16590 Bangladesh Journal of Dental Research & Education Vol.3(1) 2013: 16-20 <!--[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> <!--[if gte mso 9]> 800x600 <![endif]--> Dental caries is one of the most common health problem in the dental practices in both developed and developing countries including Bangladesh. The overall influence of dental caries on the general health of the community is harmful. The main objective of the study was to assess the factors related to dental caries among the patients attending at the Outpatient Department (OPD) of Dhaka Dental College and Hospital. The study was carried out during the month of January to June, 2002. Data were collected by the researcher himself with a pretested structured interview schedule from 167 patients selected by systematic random sampling procedure. The study showed that (29.3%) patients were in the age group of 21-30 years. Their mean age was 30.04 years, SD was ±14.60 and age range was 12-72 years. Among the patients, 55.1% were males and 44.9% were females. 76.6% patients were Muslims, 15.6% were Hindus, and only 7.8% were Christians. Regarding the educational level, the maximum (63%) were below HSC education level, only 37% were HSC and above. The patients having more than four affected teeth, maximum (34.3%) were from illiterate mothers. Patients having mother's education HSC and above were nil in this group. The rates of dental caries were high among those who consumed excess sweets and who did not maintain oral hygiene adequately. Majority of the patients knew how dental caries occur and maximum of them thought that dental caries is a preventable disease. The above study showed that no age and sex is without problem. The ignorance, illiteracy, low family income, inadequate practice of oral hygiene, consumption of excess sweets etc. are the major contributory factors for the occurrence of dental caries. As dental caries is a multifactorial preventable disease, proper preventative measures including health education programme should be intensified to minimize the disease. Further study is also needed to assess the status of the problem and to find out the factors related to the disease. <!--[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";} --> <!--[endif] -->